Independent story sharing to improve elementary school students’ speaking skill - AmbarwatiNeneng; AnanthiaWinti; SilawatiEndah; Mirawati (Proceder: Applied Linguistics, Literature, and Language Education, 2023)
The research aims to describe the implementation of Story-Based Pedagogy (SBP) in improving the students’ speaking skill; specifically in the independent story sharing stage, one of the stages of SBP. Action research design was employed in the study. The research participants involved 21 second as the research participants from one of elementary school in Kabupaten Bandung. Story sharing activity as the form of the test, observation, documentation, and field notes were conducted to collect data of the students’ speaking skills. The research was conducted in two cycles by following the procedure of action research, namely, planning, implementing, observing and reflecting. Two stories made by the first researcher were used in the learning process while the remaining researchers acted as editors. The collected data were analysed qualitatively and quantitatively. The qualitative data were organised for coding, redundancies were eliminated, and themes from categories were identified. The quantitative data were taken from students’ score of doing independent story sharing. The result of the study showed the implementation of SBP improved students’ speaking skill and confidence in doing speaking activity. It was proven by the students’ mean score, from 54.29 in the first cycle, and 84.14 in the second cycle. It was also revealed that students’ self-confidence in speaking has increased; from 11 students were able to do story sharing in the first cycle, then, all 21 students were able to conduct independent story sharing activity well at the second cycle. Thus, it can be concluded that the independent story sharing can improve elementary school students’ speaking skill.